Hubungan Kecerdasan Emosional dan Motivasi Terhadap Hasil Belajar Mata Kuliah Bahasa Inggris di Jurusan Kesehatan Lingkungan Politeknik Kesehatan Kemenkes Banjarmasin - Erminawati Erminawati; Imam Santoso (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2014)
Abstract : Relationship of Emotional Intelligence and Motivation on Learning Outcomes of English in the Environmental Health Departmen of Health Polytechnic Banjarmasin. The background of this research are 1) As a supporting subject of competencies  English  needs to get serious attention given the current health workers must have good communication skills in public. 2) English is still regarded as a difficult subject 3) There are still students who attend English language classes not because of her interest,. The purpose of the study was 1) to determine the effect of emotional intelligence on learning outcomes, 2) to determine the effect of motivation on learning outcomes, 3) to determine the effect of emotional intelligence and motivation together on learning outcomes. The design study was a descriptive study with cross sectional approach. The results showed the value of p = 0.788> α = 0.05 then H0 was accepted; meaning that there was no significant positive relationship and emotional variables on learning outcomes. Similarly, for the variable of motivation on learning outcomes there was also a positive and significant relationship was indicated by a value of p = 0.929> α = 0.05 then H0 is accepted. Suggestion 1) that prior to learning both physically and mentally to be ready to accept what is presented by lecturer, 2) should be within the student must be no impetus to learn 3) teachers should understand what factors can affect the learning outcomes to be considered in the learning process. Keywords : emotional intelligence; motivation